(untitled) (ENTHYMEMA, 2020)
Quinto Orazio Flacco is among the most translated Latin auctores in Europian literary cultures, especially in the 16th, 17th and 18th centuries. The repertory and critical reconstruction of the translations that have been the subject of its corpus is therefore offered as a particularly significant document of the fortune of the translation of a literary myth, as it attests to the relationship of imitatio/aemulatio that many Authors established with the model at the time when they decided to assimilate it, through translations, to the National languages and cultures to which they belong.